Environmental impacts of examination gloves made of natural rubber and nitrile rubber, identified by life‐cycle assessment. (23rd February 2021) - Patrawoot, Supatra; Tran, Thierry; Arunchaiya, Marisa; Somsongkul, Voranuch; Chisti, Yusuf; Hansupalak, Nanthiya
Abstract: Medical examination gloves made of natural rubber (NR; powdered and non‐powdered) and synthetic nitrile rubber (NBR) were compared in terms of their environmental impact using life cycle assessments spanning material extraction, transportation to the glove production factory, the production process, and disposal by total incineration. ReCiPe Midpoint (H) V1.13/World Recipe H life cycle assessment method implemented using the SimaPro 9.0.0.48, was used. Single scores of each glove type and stage were determined by using weighting factors specifically obtained from a 2014 survey in Thailand. With current technologies, the overall environmental impact, or the total single score, of NR gloves was higher than of NBR gloves, because the glove production stage of NR gloves required more energy and sulfur use. In addition, the overall environmental impact of both types of gloves was found to be lower if powder coating was used rather than chlorination to reduce stickiness, and if glove production relied on natural gas for energy rather than coal. The single score approach revealed the hotspots for potential improvements for each glove type. Abstract :